PERBANYAKAN VEGETATIF ANGGREK Dendrobium sp PADA BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR DAN INTENSITAS PEMUPUKAN - Zulkaidhah, Zulkaidhah; Wardah, Wardah; Muhamad, Ari (ForestSains, 2018)
This study aims to determine the vegetative growth of Dendrobium sp orchids at various concentrations of liquid organic fertilizer and fertilizer intensity. This research was designed with a completely randomized design (CRD) factorial pattern. The first factor is the concentration of liquid organic fertilizer consisting of three levels, namely the concentration of 5 ml / liter (A1), 10 ml / liter (A2), 15 ml / liter (A3), and the second factor is the intensity of fertilization consisting of 1 time / week ( B1), 2 times / week (B2), 3 times / week (B3). The results showed that the interaction between the concentration of liquid organic fertilizer and fertilizer intensity significantly affected the time parameters of buds, shoot height, and number of leaves. The 10 ml / liter concentration treatment with fertilizer intensity 3 times / week (A2B3) gave the fastest shoot growth of 7.93 weeks and had the highest yield on Dendrobium sp orchid shoot height at 12 weeks after planting which was 3.5 cm and the amount Dendrobium sp orchid leaves at the end of the observation were 4.75 strands.